LOWER LIMB TRAUMA DUE TO FIREARM PROJECTILE IN CANINDE MACAW (ARA ARARAUNA) - A CASE REPORT - COSTA, T. D.; TIMOTEO, J. L.; ROCHA, H. B. O.; SOUZA, R. H. O. (Ars Veterinaria, 2023)
The study of traumatic injuries in wildlife, especially those caused by firearm wounds is of paramount importance in understanding the impact of human activities on natural ecosystems. This case report presents a study of a gunshot wound in the lower right limb of a blue-and-yellow macaw (Ara ararauna), shedding light on the potential threats faced by these birds in their natural habitats. Following the macaw’s rescue, visual and manual examinations, along with radiography, were conducted to ensure the removal of any remaining projectiles from its body. Subsequently, the bird received a specialized medication protocol focused on the removal of myiasis and rigorous monitoring of the healing process. However, despite these efforts, the bird lost the ability to fly and developed a bony callus, making its reintroduction to the wild unfeasible, then it was sent to the São Carlos Zoo in São Paulo, Brazil, where it will coexist with other birds facing similar limitations. Understanding such incidents can provide insights into the complex interaction between human actions and the well-being of avian populations, prompting us to develop and implement effective strategies for treatment, clinical monitoring, release, and conservation.